Manajemen Strategi Bumdes Subur Makmur dalam Meningkatkan PAD di Desa Kretek Kecamatan Paguyangan Kabupaten Brebes Tahun 2023 - Mulyaningsih Mulyaningsih; Ariesta Amanda; Zaula Rizqi Atika; Indah Ayu Permana Pribadi; Chamid Sutikno (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This study is a research in the field of public administration aimed at describing the strategic management process implemented by BUMDes Subur Makmur in an effort to increase Village Original Income (PADes) in Kretek Village, Paguyangan District, Brebes Regency. The research method employs a descriptive qualitative approach with a case study design. The research targets stakeholders involved in the management of BUMDes. Informants were selected using a purposive sampling technique. Data sources consist of both primary and secondary data. This study focuses on aspects of strategic planning, program implementation, and performance evaluation of BUMDes. Data analysis is conducted using an interactive model with a descriptive design. The findings indicate that BUMDes Subur Makmur has successfully implemented strategies in several aspects; however, existing challenges still require further attention to achieve optimal performance and maximize benefits for the village community. Improvements in human resource management, financial management, and adaptation to the evolving business environment are necessary to enhance the future effectiveness of BUMDes.